Investment analysis of companies for understanding the competitiveness of a municipality of Ribnica - Vito Bobek; Miha But; Tatjana Horvat (Mednarodno Inovativno Poslovanje)
The authors explain how policy and development represent a framework for regional development. In the empirical part, the authors analyzed the economic development and competitiveness of the municipality based on an online survey previously distributed to active economic operators in the municipality. The research examined the vitality of companies, their orientation and compliance with new EU guidelines, their investment activities, their sources of funding, their ability to obtain state subsidies, and their cooperation with local and regional authorities. The paper shows that the municipality of Ribnica ranks in the top half of the municipalities based on its development and competitiveness.